Penggunaan Metode Asyarah Dalam Meningkatkan Kemampuan Membaca Huruf Hijaiyah Pada Peserta Didik - Nur Ameita P. Br Sitepu; Sri Eka Purwasih (Al-Ulum: Jurnal Pendidikan Islam, 2020)
In this article the author presents an explanation of the Asyarah Method which can be a solution to improve students' abilities in mastering hijaiyah letters. One supporting aspect that can be done to achieve learning outcomes is the use of methods. At present, educators do not utilize technology facilities to progress the potential of students, because basically students think in a concrete operational way, namely by presenting object examples of material explanations when these are not obtained by students, so they tend to lack understanding of the material being taught because of the mindset in give still abstract. Through the Asyarah Method, it can be an effective solution in making it easier to remember hijaiyah learning for students.Keywords: Hijaiyah Letters, Asyarah Method